A pedagogical model for teaching action research in Kazakhstan’s EFL teacher education - Marina Zhambylkyzy; Tolkyn Baibossynova; Anar Yessenbay; Makhabbat Adilkhan (International Journal of Evaluation and Research in Education (IJERE), 2026)
This article examines the pedagogical use of action research (AR) in enhancing professional and problem-solving skills of prospective teachers in Kazakhstani secondary schools. The study involved twenty-seven pre-service and novice English as a foreign language (EFL) teachers, all of whom were master’s students at Kazakh National University. The study was implemented within the AR course integrated into the master’s program curriculum. To support participants’ understanding and practical application of AR, we designed “AR tree” model, a visual, cognitive and pedagogical scaffold. It was introduced to make the stages of AR more accessible for novice teachers. After presenting the model, semi-structured interviews were conducted with pre-service teachers to explore its pedagogical value for professional learning. The results indicate that the model strengthened connections between theory and practice, promoted reflective professional thinking, and enable novice teachers to systematically identify classroom challenges and develop pedagogically informed solutions. The study does not propose a new form of AR, instead, the model guided pre-service teachers through each phase, from finding a problem to developing interventions, reflecting with learners, and sharing results.